2021
DOI: 10.11591/ijere.v10i4.21299
|View full text |Cite
|
Sign up to set email alerts
|

Productive teacher job satisfaction: Disentangling organizational climate, facility management, and organizational citizenship behavior

Abstract: <span>Productive teachers are teachers who teach vocational subjects. A productive teacher has complex characteristics and professional requirements so that job satisfaction must be considered. The research objective was to analyze the direct effect of organizational climate, management of facilities and infrastructure, organizational citizenship behavior on the job satisfaction of productive teachers. The research employed a quantitative approach with a survey method. The research sample was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Banyak peneliti yang meneliti tentang Organizational Citizenship Behavior (OCB) (Alanoğlu & Demirtaş, 2016;Demir, 2015;Samancioglu et al, 2019;Soparidah et al, 2021), namun masih belum ada peneliti yang mengaitkan OCB dengan program merdeka belajar. Penting untuk menelaah Organizational Citizenship Behavior (OCB) dan kaitannya dengan kepemimpinan transformasional serta efikasi diri guru di sekolah dasar penting untuk memahami perilaku guru di luar tugas-tugas formal mereka dapat membentuk iklim sekolah yang positif.…”
Section: Pendahuluanunclassified
“…Banyak peneliti yang meneliti tentang Organizational Citizenship Behavior (OCB) (Alanoğlu & Demirtaş, 2016;Demir, 2015;Samancioglu et al, 2019;Soparidah et al, 2021), namun masih belum ada peneliti yang mengaitkan OCB dengan program merdeka belajar. Penting untuk menelaah Organizational Citizenship Behavior (OCB) dan kaitannya dengan kepemimpinan transformasional serta efikasi diri guru di sekolah dasar penting untuk memahami perilaku guru di luar tugas-tugas formal mereka dapat membentuk iklim sekolah yang positif.…”
Section: Pendahuluanunclassified
“…Analyzing the impact of such materials on language learning outcomes and student engagement has been a prevailing focus in educational research. As pointed out by (Ariffin, Halim, & Darus, 202;Soparidah, Madhakomala, & Hanafi, 2021), language acquisition has always been an integral part of education, driving the ongoing quest for effective language learning methods. In the present context, there exists a significant emphasis on incorporating audio-visual components into instructional materials for language learning, garnering considerable attention from researchers and educators alike (AMIRREZA, 2019;Zhang & Chen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reality indicated that several schools in Indonesia still had teachers who had not demonstrated high OCB, even though the government has attempted to appreciate them, such as providing allowances and training to improve performance and competence (Alshaikh & Bond, 2020;Ghalavi & Nastiezaie, 2020;Samancioglu et al, 2019). Several research reports revealed that teachers' quality, professionalism, and competence, particularly in Indonesia, were still relatively low (Lestari et al, 2021;Soparidah et al, 2021) The United Nations Educational, Scientific and Cultural Organization (UNESCO) released its report in the 2016 Global Education Monitoring (GEM) Report that education in Indonesia was only ranked 10 th out of 14 developing countries.…”
Section: Introductionmentioning
confidence: 99%